2016
DOI: 10.1111/soin.12147
|View full text |Cite
|
Sign up to set email alerts
|

Blatant, Subtle, and Insidious: URM Faculty Perceptions of Discriminatory Practices in Predominantly White Institutions

Abstract: Although modest gains are observed in the number of African American, Mexican American, and Puerto Rican faculty in higher education institutions, systemic issues of underrepresentation and retention remain problematic. This article describes how historically underrepresented minority (URM) faculty in Predominantly White Institutions perceive discrimination and illustrates the ways in which discriminatory institutional practices-such as microaggressions-manifest and contribute to unwelcoming institutional clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 49 publications
2
85
0
Order By: Relevance
“…Recent figures from the U.S. Department of Education (2017) show that White male faculty are the most likely to be full professors, and therefore are more likely to set agendas for departments and institutions and receive the highest salaries. Universities pursue diversity policies to mitigate the White patriarchal hegemony of academia, but do not seem to have made a great deal of progress (Zambrana et al, 2017). Many "implicit bias" studies show preferences for White male faculty (Baker, 2015), while "publish or perish" has historically been the major criterion for White male academic careers (Wilson, 1942).…”
mentioning
confidence: 99%
“…Recent figures from the U.S. Department of Education (2017) show that White male faculty are the most likely to be full professors, and therefore are more likely to set agendas for departments and institutions and receive the highest salaries. Universities pursue diversity policies to mitigate the White patriarchal hegemony of academia, but do not seem to have made a great deal of progress (Zambrana et al, 2017). Many "implicit bias" studies show preferences for White male faculty (Baker, 2015), while "publish or perish" has historically been the major criterion for White male academic careers (Wilson, 1942).…”
mentioning
confidence: 99%
“…The analysis of these data also explored growth in the number of minority faculty from 1993 to 2009. Underrepresented minority faculty grew from 7.3% to 9.9% in this time frame, and Black faculty increased by one percentage point (Smith et al, 2012 which are not rewarded in the tenure process (Zambrana et al, 2017). These themes show the existing issues surrounding bias among professionals in higher education, and additional studies revealed similar themes (Salvucci & Lawless, 2016;Turner & Grauerholz, 2017).…”
Section: Biases Surrounding Minority Faculty and Staffmentioning
confidence: 71%
“…This essay has demonstrated that both Black male students as well as minority faculty and staff experience microaggressions on some college campuses (Barker & Avery, 2012;Brooms & Davis, 2017;Harper, 2015;Parker et al, 2016;Salvucci & Lawless, 2016;Turner & Grauerholz, 2017). Biases among professionals has been linked to the underrepresentation of minority faculty (Salvucci & Lawless, 2016;Zambrana et al, 2017), and this underrepresentation serves as a contributing factor to the climate issues experienced by Black male students (Barker & Avery, 2012;Brooms & Davis, 2017;Parker et al, 2016).…”
Section: Faculty and Black Male Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hughey et al (2015), using an experimental vignette design, found that exposure to microaggressions are correlated with racial attitudes associated with various forms of repression of people of color. Moreover, Zambrana et al (2017), using a mixedmethods approach, found that faculty of color in historically white institutions regularly encounter racial discrimination from colleagues and administrators. While this news is refreshing, the number of social scientists still neglecting the structural and institutional side of the racial microaggressions equation is far too many.…”
Section: Sociologists Enter the Conversationmentioning
confidence: 99%